The nursing experience of caring a patient with metastatic brain tumor in surgical pain management ward: a case study report - Sheng-Feng, Sun (South East Asia Nursing Research, 2020)
Brain metastases are related to the poor prognosis of patients. It is not clear why certain cancers are more likely to metastasize to the brain than others. Lung cancer, breast cancer and melanoma noted as the highest incidence of brain tumor metastasis. The purpose of this report was to describe the nursing care of a patient with malignant tumor on the left breast who received multiple chemotherapy and radiotherapy, targeted therapy and mastectomy, and the tumor metastasized to the right occipital lobe of the skull. This study was conducted in surgical pain management ward within 3 days observation. Gordon's eleven health function types’ assessment framework was used. Observations, physical assessments, interviews, medical records were attempted to collect physical, psychological, social and spiritual data. Two specific nursing problems were found. Special attention need to be paid for the pain situation and take individualized nursing measures by evaluating individual patients.